The effect of parameter changes to the performance of a triangular shape interrupted microchannel heat sink - Abdul Munir, Fudhail; Mohd Azmi, Mohd Irwan; Razali, Nadlene; Mat Tokit, Ernie (UTM, 2012)
The effect of parameter changes on triangular shaped interrupted microchannel performance was studied by simulation using FLUENT software. The parameters that were studied are total length, and the contact angle. On the other hand, the investigated effects were pressure drop and platinum film temperature. The flow in microchannel is laminar and single phase. Water was used as the working fluid and the interrupted microchannel is made of silicon. A thin platinum film plate was deposited to provide uniform heat flux. The geometry dimension of the heat sink is 30 mm in length, width of 7 mm and the thickness of 0.525 mm. From the simulation results, it is found that the improvement on heat dissipation may be achieved by increasing the microchannel length at the expense of increase in pressure drop. In addition to that, by reducing the contact angle will result to reduction in term of pressure drop and increases the improvement thermal dissipation.